Hubungan Pengetahuan Akseptor Dengan Efek Samping Penggunaan Kontrasepsi KB Suntik 3 Bulan Di Puskesmas Jetis I Tahun 2025 - Najma Aulia Nuranifa; Nuryuliana Nuryuliana; Margiyati Margiyati (CV. ITTC INDONESIA, 2025)
The three-month injectable contraceptive is a popular family planning method due to its convenience and effectiveness. However, its use often causes side effects such as menstrual cycle disturbances and weight changes, which can affect user satisfaction and continuation. The acceptor's knowledge of this contraceptive method is crucial for anticipating and managing these side effects. This study aimed to examine the relationship between the level of knowledge of acceptors and the occurrence of side effects from the use of the three-month injectable contraceptive at Jetis 1 Public Health Center in 2025. Using a quantitative analytical observational approach with a cross-sectional design, data from 53 acceptors were randomly selected using simple random sampling and analyzed with the chi-square test. Results showed the majority of acceptors had fair knowledge (49.1%) and most experienced side effects (83%). Menstrual disorders (79.8%) and weight changes (64.2%) were the most common side effects. A significant relationship was found between acceptor knowledge and side effects (p = 0.001). It is concluded that acceptor knowledge plays a significant role in experiences of side effects with the three-month injectable contraceptive. It is recommended that health workers intensify education and counseling to help acceptors effectively manage side effects.